PTEN loss is not associated with trastuzumab resistance in metastatic breast cancer - (:unkn) unknown (IMPRIMATUR PUBLICATIONS, 2014)
Purpose: Although the clinical benefits of trastuzumab are well known, intrinsic or acquired resistance is a commonly encountered clinical condition. A potential resistance mechanism is aberrant downstream signal transmission due to loss of phosphatase and tensine homologue (PTEN). This study investigated the relationship between trastuzumab response and loss of PTEN in metastatic breast cancer patients. Methods: Patients with histologically confirmed human epidermal growth factor receptor 2 (HER2) positive metastatic breast cancer, who were treated with trastuzumab were enrolled into the study. PTEN expression was immunohistochemically evaluated. Results: The patient median age was 50 years. Of 38 patients, 6 (15.8%) showed PTEN loss. No statistically significant difference was found between trastuzumab response, overall survival (OS) and progression-free survival (PFS) and PTEN loss (p=0.538). Conclusion: The activation of phosphatidylinositol 3-kinase (PI3K) pathway resulting from PTEN loss was not found to be correlated with trastuzumab response and survival. PTEN loss should not lead to exclusion of patients from the potential to benefit from trastuzumab administration.
Keywords: breast cancer; HER2; PI3K pathway; PTEN loss; trastuzumab; GENE PROTEIN PRODUCT; PI3K PATHWAY; EXPRESSION; THERAPY; PIK3CA; MUTATIONS